Effect of Supply Chain Management to Corporate Financial Performance through Corporate Environmental Disclosure: Evidence from Indonesia - St. Dwiarso Utomo; Zaky Machmuddah; Riana Sitawati (International Journal of Supply Chain Management, 2020)
Abstract— The purpose of the research is to evidence the role of corporate environmental disclosure in mediating the relationship between supply chain management and corporate financial performance. Food and beverage companies listed in Indonesia Stock Exchange in period of 2014-2018 are the sample of the current research. Path Analysis with Partial Least Squares-Structural Equation Modeling (SEM) is used to analyze data. The research finding found that supply chain management directly affects to corporate financial performance and supply chain management indirectly affect to corporate financial performance through corporate environmental disclosure. Theoritical implication of the research is that the research supports the existing theory. While practical implication of the research is that CED can be used to gain personal branding from stakeholders and to protect from SCMaction. Thus, it can increase financial and economic performance to keep company legitimate.